(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
Shakhrisabz is, above all, associated with the Ak-Saray palace. Many amazing legends are linked with the history of the palace’s construction. According to one of them, Timur began to think of building a magnificent edifice, summoned an architect and set out his objective. After listening to the ruler, the architect asked to be allowed into the state exchequer. When permission was granted, the craftsman started to make foundation blocks from clay mixed with gold in full view of Timur.